Potentialities of oligogalacturonides and chitosaccharides on plant rooting - Reyes-Pérez, Juan José; Ramos-Remache, Rommel Arturo; Llerena-Ramos, Luis Tarquino; Ramírez-Arrebato, Miguel Ángel; Falcón-Rodríguez, Alejandro Bernardo (REVISTA TERRA LATINOAMERICANA, 2021)
Oligogalacturonides and chitosaccharides are members of a new class of bioactive substances with plant activity known as oligosaccharins. The application of these substances has direct and indirect benef icial effects on plant rooting processes, which are discussed in this work. These substances have been considered second messengers of some classic plant hormones, such as auxins, cytokines and gibberellins, resulting in their much more specif ic activity in the different organs of plants. Their physicochemical and structural characteristics also have a signif icant influence on their biological activity and especially on rooting processes, both in vitro and in vivo. In our study, we discussed positive effects caused by the application of oligogalacturonides and chitosaccharides in the process of rooting, as well as indirect effects related with the increased interaction with symbiotic soil microorganisms such as rhizobacteria and arbuscular mycorrhizal fungi that improve root growth and function in plants.